Driving locus of control: The Czech adaptation - Gabrhel, Vít; Ježek, Stanislav; Zámečník, Petr (Československá psychologie, 2021)
Objectives. This study attempts to introduce the Driving Locus of Control (DLoC), a method focused on the internal or external source of attribution of the driving behaviour, to the Czech context. This study also relates DLoC to attitudes towards autonomous vehicles (AVs). tatistical analysis. Confirmatory factor analysis was used to analyse the factor structure of DLoC Scale. Hypotheses related to the empirical validity of the method were assessed via structural equation modelling. The reliability of DLoC Scale was calculated in terms of internal consistency (McDonald coefficient). Results. Confirmatory factor analysis revealed reasonably good support for structural validity of the one-dimensional DLoC-CZ15 factor model (χ2 = 426.967, df = 90, CFI = 0.964, TLI = 0.958, SRMR = 0.066, RMSEA = 0.065). In addition, the one-dimensional DLoC-CZ15 factor model showed acceptable internal consistency - ω = 0.9 (95% CI [0.89, 0.91]). The structural equation modelling found a relationship between DLoC and some of the items capturing attitudes towards AVs, too.
Keywords: Psychometrics; Česká republika; Reproducibility of Results; Czech Republic; Autonomous Vehicles; autonomní vozidla; řízení motorových vozidel; lidé; Surveys and Questionnaires; psychometrie; Automobile Driving; Humans; reprodukovatelnost výsledků; průzkumy a dotazníky